Особенности применения эксиламп в люминесцентном методе капиллярного контроля - Калиниченко А. Н. Алексей Николаевич; Соснин Э. А. Эдуард Анатольевич; Авдеев С. М. Сергей Михайлович; Калиниченко Н. П. Николай Петрович; Истомин К. А. Константин Андреевич (Электромагнитные методы, 2017)
Заглавие с экрана